2006
DOI: 10.1093/eurheartj/ehl273
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of aortic valvular stenosis by multislice cardiac computed tomography

Abstract: CT analysis of aortic valve is feasible in most cases and allows for reliable diagnosis and quantification of AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 18 publications
1
30
0
2
Order By: Relevance
“…MDCT can visualize the anatomic structure of cardiac valves with similar accuracy as TEE without the limitations of varying acoustic windows and heavy calcification that can limit anatomic assessment. 2 In addition, MDCT can be used in patient populations that are unable to undergo MRI studies, such as patients with claustrophobia, pacemakers, and implantable defibrillators. Therefore, MDCT can be an extremely useful supplemental imaging technique in the noninvasive evaluation of cardiac valves.…”
Section: Rationale For Cardiac Mdctmentioning
confidence: 99%
See 2 more Smart Citations
“…MDCT can visualize the anatomic structure of cardiac valves with similar accuracy as TEE without the limitations of varying acoustic windows and heavy calcification that can limit anatomic assessment. 2 In addition, MDCT can be used in patient populations that are unable to undergo MRI studies, such as patients with claustrophobia, pacemakers, and implantable defibrillators. Therefore, MDCT can be an extremely useful supplemental imaging technique in the noninvasive evaluation of cardiac valves.…”
Section: Rationale For Cardiac Mdctmentioning
confidence: 99%
“…MDCT can be considered an alternative to echocardiography for measuring aortic valve area because it is neither operator nor acoustic window dependent. 2 Figure 1 shows various MDCT trileaflet aortic valve abnormalities. A meta-analysis of 14 studies that involved 16, 40, and 64-slice MDCT showed a trend toward slight overestimation of the aortic valve area on planimetry by MDCT compared with TTE (bias 10.08 cm 2 ; 95% CI 0.04-0.13 cm 2 ; P 5 0.0001), and good correlation when comparing MDCT with TEE planimetric assessment of the aortic valve (bias 20.02 cm 2 ; 95% CI 0.16-0.11 cm 2 ; P 5 0.71).…”
Section: Aortic Stenosismentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several studies [10][11][12][13] performed with triphasic injection protocol, which consists of two contrast boluses at different flow rates followed by a saline chaser. In general, the aim of any injection protocol is to achieve an adequate, consistent, and homogeneous contrast enhancement in the coronary arteries and the cardiac chambers, in order to facilitate depiction of anatomy and pathology 1 .…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, there are 2 possible implementations of cardiac CT in patients with aortic stenosis: First, the AVA should be measured [2,[8][9][10][11]25] in all patients undergoing coronary or cardiac CT for any clinical indications, if aortic valve calcification is visible. Virtually 100% of patients with aortic stenosis will exhibit calcification, and vice versa at least 13% of patients with intermediate pre-test probability referred to coronary CT angiography (mean age 57 years) [12] will present with valvular calcification, with a rising prevalence with age.…”
mentioning
confidence: 99%